(untitled) (Global Journal of Human-Social Science, 2023)
Several authors claim that Christians are responsible for the developing ecological problems because they have used the idea of being made in the image of God Gen 1 26-27 as an excuse to justify exploiting the planet s resources Given the changes Owerri-West is experiencing concerning seasons like rain harmattan and dry seasons the issue of environmental crises is clear In response to the environmental difficulties in Owerri-West the article examines God s presence also known as the Immanence of God The data for the study was gathered through a literature review done through an analytical-critical discursive approach